3D printing of drill guide template for access cavity preparation in human molars: a preliminary study. Issue 5 (8th August 2018) - Chen, Hu; Li, Hong; Lin, Fei; Zhao, Yi-Jiao; Guo, Yu-Jiao; Zhang, Xin-yue; Wang, Yong; Lyu, Peijun
Abstract : Purpose: This paper aims to use cone-beam computed tomography (CBCT) and computer-aided design/3D printing technology to design and fabricate a drill guide template for access cavity preparation of permanent molars, and conduct a preliminary evaluation of its effectiveness. Design/methodology/approach: CBCT scans were performed on two permanent maxillary first molars extracted due to periodontitis. Based on the scans, guide templates of access cavities were designed. The angle of the guiding cylinders was determined based on the direction of the long axis of the tooth. A 3D resin printer with high resolution was used to print the guide templates. The printed guide templates were used by a dentist with specialized clinical experience to perform access cavity preparation in a dental simulator. Then the prepared access cavities were scanned again by CBCT, and scan data were compared to the design data. Findings: The 3D printed drill guide template had a close fit with the extracted tooth fit. The access cavity prepared using the guide template enabled the removal of the pulp chamber roof, and formed a straight-line access. Points were selected for measurement at regularly spaced intervals of 0.5 mm along the side wall of the access cavity. The mean deviation between the actual access cavities of the two permanent maxillary first molars and the designed cavities was less than 0.1 mm, with a maximum deviation of about 0.5 mm, showing a good conformance between the actual cavity and the designed cavity. Originality/value: A drill guide template was designed and fabricated by 3D printing technology, which easily guided burs to complete the access cavity preparation work forming an ideal cavity shape with satisfying accuracy, and thus may reduce the complications during pulp chamber entry.